Case study for production of calcium carbonate from carbon dioxide in flue gases and steelmaking slag. (June 2016) - Teir, Sebastian; Kotiranta, Tuukka; Pakarinen, Jouko; Mattila, Hannu-Petteri
Graphical abstract: Highlights: A concept for producing calcium carbonate from slag was further developed. Calcium carbonate production from steelmaking slag seems economically feasible. The process consumes CO2, avoiding 0.3 t CO2 per tonne calcium carbonate produced. Abstract: In this work, a concept for producing calcium carbonate from argon oxygen decarburisation (AOD) slag was further developed. In addition, its economic and environmental feasibility was evaluated. In the studied case, a stainless steel plant generating AOD slag and a paper plant requiring calcium carbonate are situated at a relatively close distance. The studied concept uses ammonium chloride as solvent for extracting calcium from the slag. In a subsequent step, the extracted calcium reacts with CO2 in lime kiln flue gas and precipitates as calcium carbonate. First, an industrial application of the concept was designed including the following units: a reverse osmosis unit enabling better recovery of ammonium chloride, an evaporator for removing excess water from the process, and a scrubber for removing ammonia vapours from the flue gases. The process was modelled, after which the investment costs and operational costs were estimated, and its environmental footprint was assessed. The results indicate that the process could in its current stage of development be economic for producing calcium carbonate for replacing ground calcium carbonate used by paper mills. If the net annual profit would be used as payment on the investment, the payback period would be 2.2 years. As the process consumes CO2 the process would have negative CO2 emissions, avoiding 0.3 t CO2 per tonne calcium carbonate produced.